Valuation Of The Economic Value Of Rammang-Rammang Natural Tourism Objects Using The Travel Cost Method (TCM) And Contingent Valuation Method (CVM) - Juardi, Juardi; Ertimi, Basem (Economics Department, Faculty of Economic and Islamic Business, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
South Sulawesi Province has many interesting tourist destinations to be visited by local and foreign tourists which present lots of beautiful oceans, mountainous nature, local wisdom, customs, traditions, and culinary tourism. Tourism is one of the affairs that can be managed by the Regional Government. This is the main reason researchers are interested in analyzing the valuation of the economic value of Rammang-Rammang in Maros Regency. This research is quantitative research with a survey method, namely conducting field observations and direct interviews with respondents using questionnaires as a data collection tool which is then analyzed quantitatively. The economic value of the rammang-rammang natural tourist attraction for the Environmental Services Produced is based on Direct Use Value (use value) as measured by the Travel Cost Method (TCM) approach for Domestic Visitors totaling 49,979 people in 2022, namely IDR. 65,228,992,312,- Per Year, with an Average Travel Cost (ATC) for Respondents of IDR. 1,305,128,- / Person Per Visit. The economic value of the rammang-rammang natural tourist attraction for the environmental services produced based on non-use value is measured using the Contingent Valuation Method (CVM) by asking about visitors' willingness to pay (Willingness to Pay) voluntarily. Domestic, totaling 49,979 people in 2022, which is Rp. 5. 968,558,819,- Per Year, with an Average Willingness to Pay Value of Respondents of IDR. 122,564,-/person Per Visit. Total Economic Value of the rammang-rammang natural tourist attraction for the Environmental Services produced based on the Direct Use Value (use value) measured using the Travel Cost Approach (Travel Cost Method, TCM) and Non-Use Value (Nonuse value) measured using the method ( Contingent Valuation Method, CVM) by asking individuals' willingness to pay voluntarily for domestic visitors totaling 49,979 people in 2022, namely IDR. 71,197,551,130.7,- Per Year. Potential Revenue Amount for Plastering Rammang-Rammang Natural Tourism Objects based on Voluntary Willingness to Pay (WTP) of visitors for Domestic visitors in 2022, totaling 49,979 people excluding the Entry Price (HTM), which is IDR. 71,197,551,130.7,- Per Year. If it coincides, the number of domestic visitors in 2023 will be 40,551 people, based on the average value of domestic visitors in 2021-2022, then the value of willingness to pay domestic visitors voluntarily to participate in preserving nature in 2023 will be IDR. 4,842,654,488,- Per Year, excluding Entry Ticket Price (HTP)